2016
DOI: 10.5664/jcsm.5398
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in the Scoring of Respiratory Events Among International Sleep Centers for Home Sleep Testing

Abstract: Study Objectives: Home sleep testing (HST) is used worldwide to confirm the presence of obstructive sleep apnea (OSA). We sought to determine the agreement of HST scoring among international sleep centers. Methods: Fifteen HSTs, previously recorded using a type 3 monitor, were deidentified and saved in European Data Format. The studies were scored by nine technologists from the sleep centers of the Sleep Apnea Global Interdisciplinary Consortium (SAGIC) using the locally available software. Each study was scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 30 publications
1
34
0
1
Order By: Relevance
“…Subjects were recruited from SAGIC sleep centers. 13,16,17 Inclusion criteria were suspicion of OSA and undergoing a sleep study. The prospective study was approved by the IRB at the University of Pennsylvania (IRB protocol number 820563) and additional IRB approvals at each site.…”
Section: Prospective Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were recruited from SAGIC sleep centers. 13,16,17 Inclusion criteria were suspicion of OSA and undergoing a sleep study. The prospective study was approved by the IRB at the University of Pennsylvania (IRB protocol number 820563) and additional IRB approvals at each site.…”
Section: Prospective Samplementioning
confidence: 99%
“…software at each site. 16,17 Digital photographs were obtained by using standardized protocols. 8,9 Statistical Analysis Figure 1 illustrates the overall extreme phenotype design.…”
Section: Prospective Samplementioning
confidence: 99%
“…Previous studies evaluated the reduction of inter‐scorer variability as the main success factor for teaching activities (Magalang, ; Penzel, ; Bosi et al, ). In our study we did not evaluate this particular question as we focused on the students’ experience.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that inter‐scorer variability is significant (Younes et al,) and agreement is only close to 70% in a setting without systematic quality assurance. Indeed, several studies have shown that rigorous training and expert consensus scoring can improve the overall agreement in sleep and event scoring to levels of 85% and higher (Magalang et al, ; Penzel, ).…”
Section: Introductionmentioning
confidence: 99%
“…The accepted method to analyze RIP is manual scoring, according to rules, which represent the consensus of experts [14,15]. Manual scoring suffers from intra-and inter-scorer variability [16][17][18] and is time consuming, limiting research on POA to small studies of 20 to 60 infants [5,6,11,13].…”
Section: Introductionmentioning
confidence: 99%